The Occurrence of Anomalies of the Permanent Maxillary Lateral Incisors in Patients with Ectopically Erupting Permanent Canines - P. Černochová; L. Izakovičová Hollá (Czech Dental Chamber, 2011)
Aim: The aim of this retrospective study was to compare the occurrence of anomalies of the permanent maxillary lateral incisor in patients with physiologically and ectopically erupting permanent canines and to verify whether any associations between these disorders and gender of a patient and ectopic canine position exist. Material and methods: The study comprised 871 consecutive Caucasian orthodontic patients with available complete diagnostic data obtained before the orthodontic treatment began who were referred to the Orthodontic Department of Clinic of Stomatology of St. Anne's University Hospital in Brno, from January 2000 to April 2010. The control group included 603 patients (376 females and 227 males, mean age 16.9 and 13.9 years respectively) with physiologically erupted permanent maxillary canines. The group with palatally displaced canines included 226 patients (146 females and 80 males, mean age 18.9 let and 19 years respectively). The group with buccally displaced canines included 42 patients (18 female and 24 males, mean age 13.6 and 14.2 years respectively). The occurrence of morphological variants of the permanent maxillary lateral incisor (normal-shaped, small, peg-shaped, congenitally missing) was assessed using the OPG images and orthodontic study casts. Results: Anomalies of the permanent maxillary incisor were detected in 12.4% of all the orthodontic patients, i.e. in 7.8% of patients with physiologically and 22.8% of patients with ectopically erupting permanent maxillary canines (P < 0.000001, OR = 3.49; 95% CI: 2.31-5.27). Both genders had the same frequency of the occurrence of these disturbances and no significant differences were found between the groups of patients with uni- and bilateral canine eruption disturbance. Conclusion: Anomalies of the permanent maxillary lateral incisor occurred statistically significant (nearly 3.5 times) more often in the patients with the ectopically erupting permanent maxillary canines compared to the orthodontic patients with the physiologically erupted canines. Considering the demonstrated association between the anomalies of the lateral incisor and canine eruption disturbances, the diagnostics of these anomalies is highly important in early diagnosis and interceptive treatment of ectopically erupting canines.